Computer Assisted Relief Generation-A Survey - Kerber, J.; Wang, M.; Chang, J.; Zhang, J. J.; Belyaev, A.; Seidel, H.-P. (Computer graphics forum, 2012)
In this paper, we present an overview of the achievements accomplished to date in the field of computer‐aided relief generation. We delineate the problem, classify different solutions, analyse similarities, investigate developments and review the approaches according to their particular relative strengths and weaknesses. Moreover, we describe remaining challenges and point out prospective extensions. In consequence, this survey is addressed to both researchers and artists, through providing valuable insights into the theory behind the different concepts in this field and augmenting the options available among the methods presented with regard to practical application. In this paper we present an overview of the achievements accomplished to date in the field of computer aided relief generation. We delineate the problem, classify different solutions, analyze similarities, investigate developments and review the approaches according to their particular relative strengths and weaknesses. Moreover, we describe remaining challenges and point out prospective extensions. In consequence, this survey is addressed to both researchers and artists, through providing valuable insights into the theory behind the different concepts in this field and augmenting the options available among the methods presented with regard to practical application.